Fundamentals of LTE standards and technologies - Chan, Peter (IEEE, 2010)
Course content reaffirmed: 06/2015--In this tutorial, you will learn about LTE air-interface standards and technologies. After completing this tutorial, you should have obtained a high level understanding of LTE, knowing its technical features, key advanced technologies, frame structure and resource grid. Both downlink and uplink transmissions will be addressed. For downlink, we will discuss OFDMA modulation, the physical channels and their general processing, the physical signals and MBSFN. We will also highlight the MIMO technologies in downlink, which includes SIMO, transmit diversity, spatial multiplexing and multiuser MIMO In uplink, we will introduce the key feature of LTE, SC-FDMA, which is a technology that strikes a balance between low peak-to-average-power-ratio and the advantages of OFDMA. We will also cover the physical channels and their processing and physical signals. We will introduce the possible use of uplink multiuser MIMO, which is a a technology transparent to the UEs and achieve significant increase in the system throughput. Finally, cell search and random access are covered